Tutorial review on existing image compression techniques (International Journal of Engineering and Computer Science, 2014)
Image compression is a technique that can reduce the storage space of images and videos. Moreover it is helpful to increase storage and transmission process performance. Image compression reduces the image fidelity, when an image is compressed at low bitrates. Hence, the compressed images suffer from block artifacts. The prime focus of image compression technique is to reduce the number of the image pixel elements without affecting the original image. It can be achieved by removing the redundancy present in the image. This paper shows review of different existing techniques which is available lossless and lossy compression such as Huffman coding, LZW coding, DCT, DWT, VQ compression etc. and based on the review guidelines are provided to choose best algorithm for an image.